Pendidikan islam anak usia dini di sekolah berkebutuhan khusus di indonesia bagian timur: peluang dan tantangan - Salsabila, Naisa Assyfa (Maliki Interdisciplinary Journal, 2025)
Islamic education for Early Childhood (PAUD) with special needs in Eastern Indonesia presents both significant opportunities and considerable challenges. This article aims to examine how Islamic education can be inclusively implemented in special needs schools, highlighting the potential of community support, educational policies, and the readiness of religious institutions. The study was conducted through a literature review and an analysis of several inclusive education practices in districts and cities across Eastern Indonesia. The findings indicate promising opportunities, such as increasing public awareness of the importance of early Islamic education, the openness of inclusive schools to admit children with special needs, and government regulations that are progressively oriented toward inclusive services. Nevertheless, the challenges remain substantial, including the limited number of teachers trained in Islamic Education methods for children with special needs, inadequate facilities to support inclusive learning, geographical barriers that restrict access, and persistent social stigma toward children with disabilities. Therefore, strengthening teacher capacity, developing adaptive curricula, and fostering collaboration among government, communities, and religious institutions are strategic steps required. This article emphasizes that inclusive Islamic early childhood education in Eastern Indonesia can be optimized if opportunities are maximized and challenges systematically addressed.